A Mathematical Approach to Establishing Constitutive Models for Geomaterials. (22nd June 2013) - Yang, Guang-hua; Jie, Yu-xin; Li, Guang-xin
Abstract : The mathematical foundation of the traditional elastoplastic constitutive theory for geomaterials is presented from the mathematical point of view, that is, the expression of stress-strain relationship in principal stress/strain space being transformed to the expression in six-dimensional space. A new framework is then established according to the mathematical theory of vectors and tensors, which is applicable to establishing elastoplastic models both in strain space and in stress space. Traditional constitutive theories can be considered as its special cases. The framework also enables modification of traditional constitutive models.